Pharmacological activities of limonin from Khasi Mandarin as therapeutic applications - Yengkhom Disco Singh; Debasmita Das; Sunanya Das; Kabyashree Diptimayee Swain; Srimay Pradhan; Punuri Jayasekhar Babu (Elsevier, 2022)
Khasi Mandarin (Citrus reticulata) is a unique fruit usually cultivated in high terrains regions of North-East India. They are different from ordinary orange in terms of its biochemical content (limonin, secondary metabolites), pharmacological activities, and physicochemical appearance (bright orange in color, hard peel, sweet aromatic juice). It has high nutritional values (NV) by enriching beta carotene as powerful antioxidant for scavenging free radicals, magnesium for blood pressure regulation, potassium for healthy cardio vascular functions, thiamin for energy conversion from food and vitamin C as immune enhancer. Despite its NV, limonin an aglycones and glycosides are largely available in Khasi Mandarin. Presence of this compound in Khasi Mandarin display numerous pharmacological activities like antimicrobial, antioxidant, anticancer, antidiabetic, anti-inflammatory, analgesic, antibacterial, anti-virus, liver protection and pesticidal. In this review, we discussed not only about the morphological aspects but detailed focused has been given on the nutritional value of Khasi mandarin, post-harvest disease and its management, metabolism and bioactive functions of the limonin as therapeutic applications.